Die Corpusanalyse multimodaler Erzählungen am Beispiel graphischer Romane - Dunst, Alexander; Hartel, Rita (DHd-Tagung 2015, Modellierung - Vernetzung - Visualisierung, Die Digital Humanities als fächerübergreifendes Forschungsparadigma)

Short Randomizable Aggregatable Signatures: Constructions and Security Analysis - Dallmeier, Fynn

Requirements Specification-by-Example Using a Multi-Objective Evolutionary Algorithm - van Rooijen, Lorijn; Hamann, Heiko (Proceedings of 24th IEEE International Requirements Engineering Conference (RE 2016))
A task at the beginning of the software development process is the creation of a requirements specification. The requirements specification is usually created by a software engineering expert. We try to substitute this expert by a domain expert (the user) and formulate the problem of creating requirements specifications as a search-based software engineering problem. The domain expert provides only examples of event sequences that describe the behavior of the required software program. These examples are represented by simple sequence diagrams and are divided into two subsets: positive examples of required program behavior and negative examples of prohibited program behavior. The task is then to synthesize a generalized requirements specification that usefully describes the required software. We approach this problem by applying a genetic algorithm and evolve deterministic finite automata (DFAs). These DFAs take the sequence diagrams as input that should be either accepted (positive example) or rejected (negative example). The problem is neither to find the minimal nor the most general automaton. Instead, the user should be provided with several appropriate automata from which the user can select, or which help the user to refine the examples given initially. We present the context of our research ("On-The-Fly Computing"), present our approach, report results indicating its feasibility, and conclude with a discussion.

CavSimBase: A database for large scale comparison of protein binding sites - Leinweber, M.; Fober, T.; Strickert, M.; Baumgärtner, L.; Klebe, G.; Freisleben, B.; Hüllermeier, Eyke (IEEE Transactions on Knowledge and Data Engineering)

Reconfigurable Accelerators in the World of General-Purpose Computing - Kenter, Tobias

Program Slicing: A Way of Separating WHILE Programs into Precise and Approximate Portions - Zhang, Guangli

NetIDE: All-in-one framework for next generation, composed SDN applications - Gutierrez, P. A. Aranda; Rojas, E.; Schwabe, A.; Stritzke, C.; Doriguzzi-Corin, R.; Leckey, A.; Petralia, G.; Marsico, A.; Phemius, K.; Tamurejo, S. (2016 IEEE NetSoft Conference and Workshops (NetSoft))

Proceedings of the 17th ACM International Symposium on Mobile Ad Hoc Networking and Computing (MobiHoc)

A non-disruptive automated approach to update SDN applications at runtime - Marsico, Antonio; Doriguzzi-Corin, Roberto; Gerola, Matteo; Siracusa, Domenico; Schwabe, Arne (NOMS 2016 - 2016 IEEE/IFIP Network Operations and Management Symposium)

Empowering network operating systems with memory management techniques - Doriguzzi-Corin, Roberto; Siracusa, Domenico; Salvador, Elio; Schwabe, Arne (NOMS 2016 - 2016 IEEE/IFIP Network Operations and Management Symposium)

Algorithm Engineering Aspects of Real-Time Rendering Algorithms - Fischer, Matthias; Jähn, Claudius; Meyer auf der Heide, Friedhelm; Petring, Ralf (Algorithm Engineering)
Defining, measuring, and comparing the quality and efficiency of rendering algorithms in computer graphics is a demanding challenge: quality measures are often application specific and efficiency is strongly influenced by properties of the rendered scene and the used hardware. We survey the currently employed evaluation methods for AQ1 the development process of rendering algorithms. Then, we present our PADrend framework, which supports systematic and flexible development, evaluation, adaptation, and comparison of rendering algorithms, and provides a comfortable and easy-to-use platform for developers of rendering algorithms. The system includes a new evaluation method to improve the objectivity of experimental evaluations of rendering algorithms.

The impact of the Gabriel subgraph of the visibility graph on the gathering of mobile autonomous robots - Li, Shouwei; Meyer auf der Heide, Friedhelm; Podlipyan, Pavel (Algorithms for Sensor Systems, Proceedings of the 12th International Symposium on Algorithms and Experiments for Wireless Sensor Networks (ALGOSENSORS))

Asymptotically Optimal Gathering on a Grid - Cord-Landwehr, Andreas; Fischer, Matthias; Jung, Daniel; Meyer auf der Heide, Friedhelm (Proceedings of the 28th ACM Symposium on Parallelism in Algorithms and Architectures (SPAA))
In this paper, we solve the local gathering problem of a swarm of n indistinguishable, point-shaped robots on a two dimensional grid in asymptotically optimal time O(n) in the fully synchronous FSYNC time model. Given an arbitrarily distributed (yet connected) swarm of robots, the gathering problem on the grid is to locate all robots within a 2x2- sized area that is not known beforehand. Two robots are connected if they are vertical or horizontal neighbors on the grid. The locality constraint means that no global control, no compass, no global communication and only local vision is available; hence, a robot can only see its grid neighbors up to a constant L1-distance, which also limits its movements. A robot can move to one of its eight neighboring grid cells and if two or more robots move to the same location they are merged to be only one robot. The locality constraint is the significant challenging issue here, since robot move- ments must not harm the (only globally checkable) swarm connectivity. For solving the gathering problem, we provide a synchronous algorithm { executed by every robot { which ensures that robots merge without breaking the swarm con- nectivity. In our model, robots can obtain a special state, which marks such a robot to be performing specific connec- tivity preserving movements in order to allow later merge operations of the swarm. Compared to the grid, for gath- ering in the Euclidean plane for the same robot and time model the best known upper bound is O(n^2).

Gathering a Closed Chain of Robots on a Grid - Abshoff, Sebastian; Cord-Landwehr, Andreas; Fischer, Matthias; Jung, Daniel; Meyer auf der Heide, Friedhelm (Proceedings of the 30th International Parallel and Distributed Processing Symposium (IPDPS))
We consider the following variant of the two dimensional gathering problem for swarms of robots: Given a swarm of n indistinguishable, point shaped robots on a two dimensional grid. Initially, the robots form a closed chain on the grid and must keep this connectivity during the whole process of their gathering. Connectivity means, that neighboring robots of the chain need to be positioned at the same or neighboring points of the grid. In our model, gathering means to keep shortening the chain until the robots are located inside a 2*2 subgrid. Our model is completely local (no global control, no global coordinates, no compass, no global communication or vision, ...). Each robot can only see its next constant number of left and right neighbors on the chain. This fixed constant is called the viewing path length. All its operations and detections are restricted to this constant number of robots. Other robots, even if located at neighboring or the same grid point cannot be detected. Only based on the relative positions of its detectable chain neighbors, a robot can decide to obtain a certain state. Based on this state and their local knowledge, the robots do local modifications to the chain by moving to neighboring grid points without breaking the chain. These modifications are performed without the knowledge whether they lead to a global progress or not. We assume the fully synchronous FSYNC model. For this problem, we present a gathering algorithm which needs linear time. This result generalizes a result, where an open chain with specified distinguishable (and fixed) endpoints is considered.

On Competitive Algorithms for Approximations of Top-k-Position Monitoring of Distributed Streams - Macker, Alexander; Malatyali, Manuel; Meyer auf der Heide, Friedhelm (2016 IEEE International Parallel and Distributed Processing Symposium (IPDPS))

Cost-efficient Scheduling on Machines from the Cloud - Mäcker, Alexander; Malatyali, Manuel; Meyer auf der Heide, Friedhelm; Riechers, Sören (arXiv:1609.01184)
We consider a scheduling problem where machines need to be rented from the cloud in order to process jobs. There are two types of machines available which can be rented for machine-type dependent prices and for arbitrary durations. However, a machine-type dependent setup time is required before a machine is available for processing. Jobs arrive online over time, have machine-type dependent sizes and have individual deadlines. The objective is to rent machines and schedule jobs so as to meet all deadlines while minimizing the rental cost. Since we observe the slack of jobs to have a fundamental influence on the competitiveness, we study the model when instances are parameterized by their (minimum) slack. An instance is called to have a slack of $β$ if, for all jobs, the difference between the job's release time and the latest point in time at which it needs to be started is at least $β$. While for $β < s$ no finite competitiveness is possible, our main result is an $O(\frac{c}{ε} + \frac{1}{ε^3})$-competitive online algorithm for $β = (1+ε)s$ with $\frac{1}{s} ≤ ε ≤ 1$, where $s$ and $c$ denotes the largest setup time and the cost ratio of the machine-types, respectively. It is complemented by a lower bound of $Ω(\frac{c}{ε})$.

Predicting Rankings of Software Verification Tools Using Kernels for Structured Data - Czech, Mike

Ein ultraschallbasiertes inverses Messverfahren zur Charakterisierung viskoelastischer Materialparameter von Polymeren - Bause, Fabian

5.3.1 - Ein ultraschallbasiertes inverses Messverfahren zur Charakterisierung viskoelastischer Materialparameter von Polymeren - Bause, F.; Henning, Bernd

3.2.3 - Direktgravimetrischer Partikelmasse-Sensor zur quasikontinuierlichen Emissionsmessung - Ester, S.; Struschka, M.; Henning, Bernd